Impact assessment of fish cages on coralligenous reefs through the use of the STAR sampling procedure - PIAZZI, LUIGI; CECCHI, ENRICO; CINTI, MARIA FRANCESCA; STIPCICH, PATRIZIA; CECCHERELLI, GIULIA (Mediterranean Marine Science, 2019)
The study aimed at contributing to the development of methods to assessing the effects of human disturbance on coralligenous reefs. The effects of the presence of a fish farm on coralligenous reefs were evaluated using the STAR (STAndaRdized coralligenous evaluation procedure) sampling procedure. An asymmetrical sampling design was used to compare the aquaculture site with two reference sites in areas unaffected by human pressure. The response of different ecological indices (ESCA, Ecological Status of Coralligenous Assemblages; ISLA, Integrated Sensitivity Level of coralligenous Assemblages; COARSE, COralligenous Assessment by Reef Scape Estimate) and descriptors (α-diversity, β-diversity and Sensitivity Level) of this kind of disturbance was compared. Results indicate that coralligenous reefs are vulnerable to aquaculture fish cages, and differences in the structure of coralligenous assemblages between the disturbed and the reference sites were mostly due to the decrease in β-diversity. On the contrary, no significant differences in the number of taxa/groups were highlighted. Encrusting Corallinales, erect Rhodophyta, Dictyotales, Fucales and Halimeda tuna were more abundant in reference sites than in disturbed site, while Peyssonnelia spp. and algal turfs had the opposite trend. Conversely, no significant differences between conditions were found in the abundance of sessile invertebrates. The study supports the suitability of the STAR approach to be employed in impact evaluation assessments, such as in monitoring programs. The present study is a first attempt to combine three different ecological indices (ESCA, ISLA and COARSE) within a unified approach, in order to assess the status of coralligenous reefs subjected to a moderate human-induced disturbance. The inconsistent response of the different indices highlights the advantage of applying different indices and descriptors to evaluate the variable human pressures on natural systems.